Evaluasi Usability Aplikasi Augmented Reality Morphfun Menggunakan System Usability Scale: Usability Evaluation of Morphfun Augmented Reality Application Using System Usability Scale - Raharja, Pradana Ananda; Pramudya, Baihaqi Zuhdi (POLITEKNIK NEGERI JAKARTA, 2022)
Learning metamorphosis material that is applied to elementary schools is still conventional and not interactive. Metamorphic material requires a clearer picture of the structure of animals and the process of metamorphosis itself. Before the application is distributed to a wider range of customers, it is necessary to evaluate the application in the form of an android-based metamorphosis learning media application. The purpose of this study was to evaluate the usability of the Morphfun augmented reality application using the System Usability Scale (SUS) method. The evaluation was carried out through questionnaires distributed to 10 respondents consisting of 9 students and 1 teacher for grade 6 at SDN Waru Kidul. The results of the evaluation obtained an average score of 72.25 and received a grade C category with the predicate